Probing the effects of fish oil on the delivery and inflammation-inducing potential of imiquimod - Rehman, Khurram; Mohd Aluwi, Mohd Fadhlizil Fasihi; Rullah, Kamal; Lam, Kok Wai; Mohd Amin, Mohd Cairul Iqbal; Zulfakar, Mohd Hanif (Elsevier, 2015)
Imiquimod is a chemotherapeutic agent for many skin-associated diseases, but it has also been associated with inflammatory side effects. The aim of this study was to prevent the inflammatory effect of commercial imiquimod (Aldara®) by controlled release of imiquimod through a hydrogel/oleogel colloidal mixture (CA bigel) containing fish oil as an anti-inflammatory agent. Imiquimod permeability from Aldara® cream and bigel through mice skin was evaluated, and the drug content residing in the skin via the tape stripping technique was quantified. The fish oil fatty acid content in skin along with its lipophilic environment was also determined. An inflammation study was conducted using animal models, and Aldara® cream was found to potentially cause psoriasis-like inflammation, which could be owing to prolonged application and excessive drug permeation. Controlled release of imiquimod along with fish oil through CA bigel may have caused reduced imiquimod inflammation. NMR studies and computerized molecular modeling were also conducted to observe whether the fish oil and imiquimod formed a complex that was responsible for improving imiquimod transport and reducing its side effects. NMR spectra showed dose-dependent chemical shifts and molecular modeling revealed π–σ interaction between EPA and imiquimod, which could help reduce imiquimod inflammation.